Beyond Square Meters; Social Value Creation in Commercial Real Estate in a Hybrid Work Contex - Spångberg, Gabriel; Sahlstrand, Philip (My University, 2026)
Hybrid work has changed the role of the office and challenged the traditional logic of commercial real estate, where office value has often been connected to leased square meters. When employees can work from home, the office needs to offer added value that motivates people to be present. This thesis investigates how commercial real estate (CRE) owners can create and deliver social value in office environments in a hybrid work context, and how this can create value for both tenants and CRE owners. The study is based on a mixed method approach consisting of benchmarking, semi structured interviews and a tenant survey. The benchmarking was used to examine how CREowners communicate office offerings, while the interviews provided insights from CRE owners and industry experts. The survey was used to capture the employee per spective and identify which aspects of the office environment are perceived as valuable. The findings show that social value is mainly connected to social interaction, spon taneous meetings, knowledge exchange, a sense of belonging, and workplace culture. These aspects are important because they represent values that are difficult to fully re place in the home office. However, the study also shows that social value depends on a functional foundation. Calmness, ergonomics, good acoustics, small meeting rooms, and quiet zones are necessary for the office to function as a workplace. The thesis concludes that CRE owners need to understand the office as more than a physical space. Social value needs to be translated into concrete spaces, services, and offerings that tenants and employees can use in practice. This requires closer tenant dialogue, co-creation, and a service logic perspective where value is created when the office is used. For CRE owners, social value can support tenant satisfaction, tenant retention, and differentiation, although the connection to business value should be understood as indirect. The study also shows that social value must be economically feasible, making flexible, generic, and reusable office solutions important
Keywords: Commercial real estate (CRE), social value, hybrid work, office environment, service logic, tenant retention, value creation